Specificity of Alternative Splice Form Detection Using RT-PCR with a Primer Spanning the Exon Junction. (June 2003) - Shulzhenko, Natalia; Smirnova, Anna S.; Morgun, Andrey; Gerbase-DeLima, Maria
A recently described strategy for splice variant specific detection by RT-PCR is based on the use of a primer spanning the junction between exons of the alternative splice form. However, this reaction may generate false-positive results in the presence of excess principal transcript. In this report, transcript variant 3 of T cell immune regulator gene 1 was used as a model to demonstrate a new method to ensure PCR specificity. Our approach permits the determination of detection specificity considering the full-length transcript amount. Furthermore, we demonstrated that the addition of a few molecules of a specific template dramatically increases the specificity of the reaction and allows for the detection of the alternative form, even in the presence of large amounts of the principal transcript. Competitor DNA for the alternative splice form is suggested as the specific template to achieve the detection specificity. Thus, we describe a simple strategy to avoid nonspecific amplifications for RT-PCR using a primer spanning the exon junction.